Build Me Up: Overcoming Writing Problems Among Pupils In A Rural Primary School In Belaga, Sarawak, Malaysia - Lim Kok Ien; Melor Md Yunus; Mohamed Amin Embi (Pascasarjana UM, 2017)
Abstract: This study aims to investigate the effect of the ‘Build Me Up’ in helping Year 5 pupils in a rural primary school overcome problems in constructing correct sentences. To achieve the aim of the study, a pre-test and post-test were used to collect the quantitative data required. Therefore, 16 pupils from a rural school in Belaga, Sarawak, Malaysia, with weak writing skills were selected to participate in this study. The analysis of the data indicated that the ‘Build Me Up’ tool did help the pupils overcome their problems in writing grammatically correct sentences. The use of ‘Build Me Up’ aids pupils in writing sentences using present tense, past tense, present continuous tense and past continuous tense correctly. Besides that, it also helps the pupils to understand the sentence pattern better in order to improve their writing. The findings of the study may be beneficial to ESL teachers and educators, as it can be as an alternative which can assist them in teaching writing. In addition, it also encourages the pupils to take charge of their own learning. It is suggested that future research should include the perceptions of the pupils and the teachers towards the tool as well.Key words: overcome, writing, writing tool, rural primary school, sentence construction Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh 'Build Me Up' dalam membantu siswa kelas 5 di sekolah dasar pedesaan untuk mengatasi masalah dalam membangun kalimat yang benar. Untuk mencapai tujuan penelitian ini, sebuah pre-test dan post-test digunakan untuk mengumpulkan data kuantitatif. Oleh karena itu, 16 murid dari sekolah pedesaan di Belaga, Sarawak, Malaysia, dengan kemampuan menulis yang lemah dipilih untuk berpartisipasi dalam penelitian ini. Analisis data menunjukkan bahwa 'Build Me Up' membantu siswa mengatasi masalah mereka dalam menulis kalimat yang benar secara tata bahasa. Penggunaan 'Build Me Up' membantu murid dalam menulis kalimat dengan menggunakan present tense, past tense, present continuous tense dan past continuous tense dengan benar. Selain itu, juga dapat membantu siswa memahami pola kalimat dengan lebih baik agar bisa memperbaiki tulisan mereka. Temuan penelitian ini mungkin bermanfaat bagi guru dan pendidik ESL, karena dapat menjadi alternatif yang dapat membantu mereka dalam mengajar menulis. Selain itu, juga mendorong murid untuk mengendalikan pembelajaran mereka sendiri. Disarankan agar penelitian masa depan harus mencakup persepsi siswa dan guru terhadap alat ini juga.Kata kunci: mengatasi, menulis, menulis alat, sekolah dasar pedesaan, konstruksi kalimat